Competição, cooperação e educação física : uma equação necessária à formação escolar - Piva, Jaine de Lima (2016)
Scholar Physical Education is a subject that has unique characteristics, and one of its responsibilities is to create opportunities for students to develop their potential, democratic and not selectively, aiming for their full development. With regard to the behavior expression of young people in sports, in which the subjects should experience human values guided by respect for themselves and others, it is worth asking if the competition provided by the activities related to this curriculum component leads students to have behaviors consistent with these goals. Faced with this question, this research appropriated cooperative games as the main theme, to understand the practices of Physical Education in the specific context of elementary school. The study starts of some issues that shape the research problem: how do cooperative games influence the relationship among the students? What do reactions the youth set when subjected to cooperative games practices in Physical Education? To what extent do cooperative activities contribute to the emergence of more respectful and supportive relationships among young people? Beginning by these questions, the objective of the research is to analyze the role of cooperative games as a strategy to promote the integration of students in physical education classes, and to investigate the potential of physical education for the students schooling, from an educational experience guided by cooperative games activities. The methodology adopted brings together a case study of qualitative approach, developed through four educational interventions with the application of didactic sequence involving students of the 6th year of elementary school, of a private school located in a city in the northern region of Rio Grande do Sul. After each intervention, it was promoted the participation of students in a focus group. These procedures were recorded by video recording and preparation of field diary, resulting in the primary database for this study. To understand and deepen the central theme of the study it sought the contribution of several authors, including: Orlick (1989), Brotto (1999), Soler (2009, 2011), Lovisolo (2009 Lovisolo, Borges and Muniz (2013) Huizinga (2010), Kishimoto (1997) and Macedo (2005). From this theoretical basis and primary data produced, it is concluded that through the practice of cooperative games it can qualify the behavior patterns that emerge in Physical Education classes, creating, therefore, a culture of cooperation rather than competition, favoring the relationship among subjects and confirming such strategy as a powerful teaching and learning tool of the refer curricular component.